2017
DOI: 10.1371/journal.pone.0186089
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble-based modeling and rigidity decomposition of allosteric interaction networks and communication pathways in cyclin-dependent kinases: Differentiating kinase clients of the Hsp90-Cdc37 chaperone

Abstract: The overarching goal of delineating molecular principles underlying differentiation of protein kinase clients and chaperone-based modulation of kinase activity is fundamental to understanding activity of many oncogenic kinases that require chaperoning of Hsp70 and Hsp90 systems to attain a functionally competent active form. Despite structural similarities and common activation mechanisms shared by cyclin-dependent kinase (CDK) proteins, members of this family can exhibit vastly different chaperone preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 177 publications
1
15
0
Order By: Relevance
“…We used FIRST (Floppy Inclusion and Rigid Substructure Topography) approach (Jacobs et al, 2001; Rader et al, 2002; Chubynsky and Thorpe, 2007) and the Python-based Constraint Network Analysis (CNA) interface (Hespenheide et al, 2002; Kruger et al, 2013; Pfleger et al, 2013a,b) to analyze partition of rigid and flexible regions in a set of protein kinases with the predicted cancer driver mutations. The employed parameters are consistent with our previous studies of protein kinases (Stetz et al, 2017). Protein stability computations that evaluated the effect of cancer driver mutations on the functional forms of the ErbB kinases were performed using CUPSAT (Cologne University Protein Stability Analysis Tool) (Parthiban et al, 2006, 2007).…”
Section: Methodssupporting
confidence: 85%
“…We used FIRST (Floppy Inclusion and Rigid Substructure Topography) approach (Jacobs et al, 2001; Rader et al, 2002; Chubynsky and Thorpe, 2007) and the Python-based Constraint Network Analysis (CNA) interface (Hespenheide et al, 2002; Kruger et al, 2013; Pfleger et al, 2013a,b) to analyze partition of rigid and flexible regions in a set of protein kinases with the predicted cancer driver mutations. The employed parameters are consistent with our previous studies of protein kinases (Stetz et al, 2017). Protein stability computations that evaluated the effect of cancer driver mutations on the functional forms of the ErbB kinases were performed using CUPSAT (Cologne University Protein Stability Analysis Tool) (Parthiban et al, 2006, 2007).…”
Section: Methodssupporting
confidence: 85%
“…PRS formalism is rooted in the linear response theory to estimate residue response to external forces applied systematically to each residue in the protein system 74 , 75 . This approach was successfully used in probing allosteric mechanisms in single protein domains and large multi-domain assemblies 76 79 . The average perturbation response maps are matrices in which the ij th element refers to the average response (displacement) of residue j to external perturbation at residue i .…”
Section: Resultsmentioning
confidence: 99%
“…These studies included experiment-guided structural modeling and protein folding analysis (Levinson et al, 2006 ; Zhang et al, 2006 ; Kornev et al, 2008 ; Han et al, 2011 ; Jura et al, 2011 ; Shan et al, 2011 , 2012 , 2013 ; Taylor and Kornev, 2011 ; Tzeng and Kalodimos, 2011 ; Levinson and Boxer, 2012 , 2014 ; Taylor et al, 2012a , b ; Meharena et al, 2013 ; Shaw et al, 2014 ; Shukla et al, 2014 ; Kornev and Taylor, 2015 ; Schulze et al, 2016 ; Narayanan et al, 2017 ; Levinson, 2018 ; Ruff et al, 2018 ), molecular simulations and free energy computations (Yang and Roux, 2008 ; Dixit and Verkhivker, 2009 , 2011a , b ; Yang et al, 2009 ; Arkhipov et al, 2013 ; Lin and Roux, 2013 ; Lin et al, 2013 , 2014 ; Dixit and Verkhivker, 2014 ; Meng and Roux, 2014 ; Fajer et al, 2017 ; Kim et al, 2017 ; Meng et al, 2017 ), and network modeling (James and Verkhivker, 2014 ; Tse and Verkhivker, 2015a , b , c ; Czemeres et al, 2017 ; Stetz et al, 2017 ; Astl and Verkhivker, 2019a , b ). By examining residue interaction networks in protein kinases a unifying mechanistic model of allosteric coupling between the ATP-binding and substrate binding sites conserved among kinases was proposed (Tse and Verkhivker, 2015a , b , c ; Stetz et al, 2017 ). A theoretical framework for rationalizing binding preferences of the kinase inhibitors was developed establishing the relationships between ligand binding and modulation of the residue interaction networks (Tse and Verkhivker, 2015a , b , c ).…”
Section: Network-based Approaches In Studies Of Allosteric Regulationmentioning
confidence: 99%
“…Computational studies of allosteric regulation in molecular chaperones Hsp90 and Hsp70 have also been instrumental to the progress in the field by complementing biochemical experiments and providing a detailed dynamic view of the functional cycle and mechanisms (Colombo et al, 2008 ; Morra et al, 2009 , Verkhivker et al, 2009 ; Morra et al, 2010 , 2012 ; Matts et al, 2011a , b ; Chiappori et al, 2012 , 2016 ; Dixit and Verkhivker, 2012 ; Lawless et al, 2013 ; Verkhivker, 2014 , 2018a , b ; Paladino et al, 2015 ; Stetz and Verkhivker, 2015 , 2016 , 2017 , 2018 ; Czemeres et al, 2017 ; Stetz et al, 2017 ). Using a network-based formalism of allostery, computational studies have captured NMR-observed direction-specific nature of signal propagation pathways in the Hsp70 chaperone (Stetz and Verkhivker, 2015 , 2017 ).…”
Section: Network-based Approaches In Studies Of Allosteric Regulationmentioning
confidence: 99%